Project-based learning at the pedagogical university of the Republic of Kazakhstan - Mussina, Guldana; Tazhenova, Gulnara; Roza Bekmagambetova, Almagul Aitpayeva, Magziya Kunanbayeva, (Opción, 2019)
This article describes the results of a study of the specificity of implementation of project-based learning at a pedagogical university in Kazakhstan and the difficulties arising from this via comparative qualitative research methods. As a result, lecturers of the pedagogical university have knowledge of project-based learning, but they rarely use this method of teaching, however, most of the respondents consider this method to be promising. In conclusion, the content of educational programs includes disciplines projected to develop the personal and moral professional qualities of future teachers, general cultural and professional competences.